Self-perceived assessment competencies and practices among university lecturers - Matuvo, Musa; Zubairi, Ainol Madziah (Emerald Insights, 2014)
Purpose – The purpose of this paper is to analyse the lecturers’ self-perceived competencies and practices in assessing students. Design/methodology/approach – An Assessment Practices Inventory Modified was administered to a sample of 329 randomly selected lecturers from six universities in Uganda. Factor analysis and multivariate analysis of variance (MANOVA) were used to address the research questions. Findings – The results of factor analysis yielded a factor structure of four variables; design, administration, interpretation, and application. The MANOVA multivariate test results highlighted differences in assessment competencies and practices among lecturers in the different academic levels (Wilks’ l¼0.732, F(16, 313)¼5.624, po0.05, Z2¼0.075), and in the interaction between type of university, specialisations, and academic levels (Roy’s largest root¼0.073, F(8, 313)¼2.543, po0.05, Z2¼0.068). The Tukey HSD post hoc test results revealed that lecturers in the specialisation of education were different from their counterparts in other specialisations, in interpreting assessment results. Academic levels differences existed in all the dependent variables (design, administration, interpretation, and application). No differences existed in assessment competencies and practices between lecturers in the different types of universities. Originality/value – Lecturers have been found to differ in their assessment competencies and practices, according to their specialisations and academic levels. It has been recommended in this study, that, assessment training programmes be made mandatory to all lecturers in universities, in order to bridge the gap their competencies and practices in assessing students.